The School-Family Interface and Its Sociopedagogical Implications: The Case of Public Primary School of Soavinandriana-Itasy - Zo, Ratsimandisa Haritiana; Razanamiariso, Rakotomalala Nivomboahangy; Myriam, Andrianjary; Bodomalala, Razanadrasoa Vololonome; Narindra, Ratiarimanajatovo; Tojoniaina, Ramiadamahefa; Allain, Solofomiarana Rapanoel Bruno; Baholy, Robijaona Rahelivololoniaina (BIRCU, 2025)
This inquiry, conducted within a Public Primary School (PPS) of Soavinandriana, investigates the multifaceted dynamics of the school-family relationship and its consequential influence on student learning and development. Examining parental perspectives, school expectations, communication strategies, and the overarching impact of school climate across preschool and elementary settings reveals a complex interplay of historical experiences, evolving societal contexts, and individual perceptions. The establishment of robust educator-family connections, facilitated by transparent communication and collaborative initiatives, emerges as a cornerstone of effective partnerships. Parental expectations, primarily centered on academic progress and child well-being, underscore the shared objectives of home and school in Soavinandriana. The study highlights the critical role of trust, cultivated through mutual respect and consistent dialogue, in fostering meaningful parental engagement within the PPS. Furthermore, it underscores the cyclical nature of positive involvement, wherein effective communication and school-initiated integration efforts lead to increased parental participation and enhanced student outcomes specific to this Malagasy school. Conversely, ambiguities in communication and differing parental representations of schooling can present challenges to this vital partnership within the Soavinandriana context. Ultimately, optimizing student learning and fostering holistic development within this PPS necessitates a concerted effort to cultivate a synergistic home-school ecosystem. This involves proactively addressing parental expectations, promoting clear and consistent communication, and nurturing a positive and inclusive school climate that values the diverse experiences and perspectives of both families and educators in Soavinandriana. Recognizing the reciprocal influences within this relationship is paramount for creating a supportive and cohesive educational environment within this particular Malagasy primary school.